Observations of phase changes in monoolein during high viscous injection. (21st March 2022) - Wells, Daniel J.; Berntsen, Peter; Balaur, Eugeniu; Kewish, Cameron M.; Adams, Patrick; Aquila, Andrew; Binns, Jack; Boutet, Sébastien; Broomhall, Hayden; Caleman, Carl; Christofferson, Andrew; Conn, Charlotte E.; et al.
Abstract : This is a study of the phase changes detected in monoolein samples under constant flow using a high‐viscousity injector. The sample behaviour was studied using X‐ray techniques while light microscopy and modelling studies were used to help interpret some of the effects observed in the data. Abstract : Serial crystallography of membrane proteins often employs high‐viscosity injectors (HVIs) to deliver micrometre‐sized crystals to the X‐ray beam. Typically, the carrier medium is a lipidic cubic phase (LCP) media, which can also be used to nucleate and grow the crystals. However, despite the fact that the LCP is widely used with HVIs, the potential impact of the injection process on the LCP structure has not been reported and hence is not yet well understood. The self‐assembled structure of the LCP can be affected by pressure, dehydration and temperature changes, all of which occur during continuous flow injection. These changes to the LCP structure may in turn impact the results of X‐ray diffraction measurements from membrane protein crystals. To investigate the influence of HVIs on the structure of the LCP we conducted a study of the phase changes in monoolein/water and monoolein/buffer mixtures during continuous flow injection, at both atmospheric pressure and under vacuum. The reservoir pressure in the HVI was tracked to determine if there is any correlation with the phase behaviour of the LCP. The results indicated that, even though the reservoir pressure underwent (at times) significant variation, this did not appear to correlate with observed phase changes in the sample stream or correspond to shifts in the LCP lattice parameter. During vacuum injection, there was a three‐way coexistence of the gyroid cubic phase, diamond cubic phase and lamellar phase. During injection at atmospheric pressure, the coexistence of a cubic phase and lamellar phase in the monoolein/water mixtures was also observed. The degree to which the lamellar phase is formed was found to be strongly dependent on the co‐flowing gas conditions used to stabilize the LCP stream. A combination of laboratory‐based optical polarization microscopy and simulation studies was used to investigate these observations.